2018
DOI: 10.1080/10803548.2018.1503401
|View full text |Cite
|
Sign up to set email alerts
|

Gender response and safe carrying load limit for sugar industry workers

Abstract: This study investigates the safe carrying load limit in relation to gender of workers in the sugar industry. A total of 632 workers (male and female) were interviewed following a physiological and psycho-physiological methodology. All of these workers were in the age groups of 21-30, 31-40 and ≥41 years. In this study, for the physiological methodology, both field and laboratory data were collected, which included heart rate, heart rate variability, energy expenditure and maximum rate of oxygen consumption. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 15 publications
0
18
0
Order By: Relevance
“…Our comfort limit definition reflects the key information we desired to understand as device designers. There are a variety of alternative or complementary ways to assess comfort and limits of comfort (e.g., [12], [17], [18]).…”
Section: Discussionmentioning
confidence: 99%
“…Our comfort limit definition reflects the key information we desired to understand as device designers. There are a variety of alternative or complementary ways to assess comfort and limits of comfort (e.g., [12], [17], [18]).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, several studies have shown that carrying a load on the head causes the least deviation from normal gait as compared with carrying on the shoulder or hand [3]. Another study recommends a higher safe load carrying limit on the head than that permissible on the back [1]. A thorough understanding of the biomechan-ics of the cervical spine and the effect of head loading on these biomechanics and any attendant degenerative process would enable us to understand the true effects of repeated axial loading of the spine.…”
Section: Discussionmentioning
confidence: 98%
“…However, workers in the construction industry and agriculture, as well as railway porters, continue to carry loads on their heads as an integral part of their job. According to a survey in 2009-2010, there are around 465 million workers in India, with the majority (94%) being employed in the unorganized sector [1]. There seems to be some awareness among these workers about safety at the workplace; however, the importance of their health condition continues to be ignored.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2) Validating the AWCRS detection of a proposed tool or intervention for industrial usage [43], [44], [45], [46]. 3) Exploring the effect of AWCRS to find an optimal work content level [47], [48], [49], [50], [51], [52], [53]. 2) Study Type: Two main study types were reported: 1) observational and 2) experimental.…”
Section: B Study Characteristicsmentioning
confidence: 99%